Venha e traga seu instrumento: reflexões sobre a orquestra-escola do Ceará e seu processo poético-pedagógico - Pereira, Elismário dos Santos (2018)
The research had the purpose of analyzing the effects perceived by a collective music practice that essentially performs the music of composers who tell stories from Ceará through the melodies of song and intruments. This investigation of the artistic project of the Orchestra-School of Ceará and its potentialities discusses the experience of musicians participating in their poetic-pedagogical process of formation, seeking to understand the musical habitus generated by the experiences and musical practices in the formal and affective filds throughout existence of each one in the orchestra. This research was conducted through by the reflections and subjectivities extracted from the reports of the agents involved from the perspective of an interrelationship of the epistemologies of Praxiology and approach in Life Stories in Formation, adopting narrative interviews with students and teachers who participated effectively in didactic presentations, workshops and concerts held from January 2016 to March 2017 in the Fortaleza, in the form of a participant research